PTH-048 Colonoscopist key performance indicators and the surveillance of patients with family history of colorectal cancer. (June 2019) - Norton, Benjamin; Wright, Thomas; Coultas, James; Nicholas, Victoria; Monahan, Kevin
Abstract : Introduction: Colorectal cancer (CRC) accounts for over 40, 000 new cases/year in the UK, and 35% of cases develop due to inherited susceptibility. Patients at hereditary risk undergo colonoscopic surveillance to reduce CRC incidence and mortality. High quality colonoscopy, measured by key performance indicators (KPI) including adenoma detection rate (ADR), caecal intubation rate (CIR), and polyp recovery rate (PRR) may enhance surveillance outcomes. This is important for high risk patients where colonoscopy may be a one-off intervention, or where there is significant risk of interval cancers. Consequently, we assessed colonoscopy quality in a cohort at hereditary risk of CRC managed at West Middlesex University Hospital (WMUH), and determined their relationship to colonoscopist KPIs in non-surveillance cohorts. Methods: We analysed prospective colonoscopic surveillance data through the Family History of Bowel Cancer Registry at WMUH between 2010–19. A cohort of 361 patients at hereditary risk were divided into five risk groups based on current BSG guidelines. Patient demographics including age, gender and family history were collated alongside colonoscopist data, colonoscopy findings, and KPIs. Using linear regression (SPSS software), we compared findings to ADRs, CIRs and PRRs of colonoscopists in non-surveillance patients. Results: During surveillance, 640 colonoscopies were performed by 12 clinicians. The collective ADR during index, 1st, 2nd and 3rd surveillance colonoscopies was 18.9%, 16.0%, 29.6% and 25.8%, respectively. There was no difference in ADRs at Index, 1st and 2nd surveillance colonoscopy between familial risk groups. The average ADR for colonoscopists across all surveillance colonoscopies was 22.6% (8.3–35.7%) and CIR was 97.92% (50–100%). In the non-surveillance cohort ADR was 29.5% (13.3–40.7%), CIR 93.5% (78.8–95.7%) and PRR 95.2% (86.9–98.2%). Colonoscopist ADRs during surveillance correlated with both ADRs (R 2 0.48, P<0.05; figure 1) and PRRs (R 2 0.47, P<0.05) in the non-surveillance cohort but not CIR. Conclusion: ADR is the main indicator of efficacy during colonoscopy and a consistent independent risk factor for interval CRCs in screening colonoscopies. Colonoscopists ADRs in patients undergoing surveillance correlated with their ADRs and PRRs during colonoscopies in a non-surveillance cohort. Therefore, we suggest that all surveillance colonoscopies are performed by endoscopists consistently achieving BSG colonoscopy KPI minimum standards.